Syntactic features in Asian television football sport commentary - Paramasivam, Shamala; Osman, Nursuhaila (Penerbit Universiti Kebangsaan Malaysia, 2018)
The chapter examines the syntactic features of Asian football commentaries. It relies on the theory of register (Biber and Conrad 2009) and the principles of register analysis and discourse analysis for data collection and analysis. The data comprises three recordings of the Asian Football Confederation Cup matches in 2016 that were conducted in English. The features found in the data were statements in the form of minor sentences (like ellipsis, substitutions, passive constructions, deictic adverbs, prefaces, and result expressions), rhetorical questions, double intensifiers, heavy modifiers, and epistemic language structures (such as modals and adverbials). The chapter shows that the football commentary is a register in its own right and that some aspects of the language use in in fact jargon-like, implying that without shared knowledge of the game and its language, it can be difficult for the public to understand the commentary. For fans, however, the study shows that the linguistic features of the register have a dual function to not only inform them but also to entertain.